Evapotranspiração em vegetação natural do bioma Caatinga obtida por balanço hídrico no solo e por sensoriamento remoto - Teixeira, Léa Moraes Nunes (2018)
Evapotranspiration is one of the most complex hydrological processes, and its understanding contributes to the analysis of the hydrological cycle. However, under natural conditions, there is still much to know, especially in regions with water scarcity, such as in the Brazilian Northeast semi-arid, in the Caatinga biome. Therefore, the objective of this research was to evaluate the evapotranspiration in natural and preserved vegetation in the caatinga biome through soil water balance and satellite images. The study area was the Aiuaba Experimental Basin (AEB), 12 km2, located in the Aiuaba Ecological Station in northeastern Brazil. At AEB, precipitation is concentrated between February and May with an annual mean of 560 mm and potential annual evapotranspiration of 2600 mm. In this research were used field data and data obtained by remote sensing. From data on rainfall and soil moisture, and data from automatic meteorological stations at Funceme PCD in Aiuaba, Taua and Campos Sales, it was possible to calculate: i) water stress coefficient, ii) potential evapotranspiration by Penman- Monteith, iii) real evapotranspiration (ETr) through the soil water balance. The runoff and the infiltration of the water balance in the soil were estimated by the Green-Ampt method and the Horton method. The actual evapotranspiration by water balance from 2004 to 2016 was related to the evapotranspiration obtained by satellite image from 2006 to 2016. Ten images were obtained by Landsat 5 TM and 18 by RapidEye processed by the SEBAL (Surface Energy Balance Algorithm for Land) model and SAFER (Simple Algorithm For Retrieving Evapotranspiration), respectively, using ERDAS IMAGINE software 14.1. The mean values of water stress coefficient (Ks) were 0.27 (±0.04) and 0.53 ((±0.19) for the dry and rainy periods, respectively. Potential daily evapotranspiration was 5.5 ((±0.5) mm. The daily real evapotranspiration by water balance in the soil presented average values around 2.5 mm for the dry period and 7.2 mm for the rainy season with the highest variations of ETr. According to FAO-56, daily ETr values for deciduous forests range from 6.0 to 8.0 mm, but there is no ETr data for deciduous plants in the dry season. The ETr values in the dry period are lower due to the very low water availability in the soil in this period. In 40% of the period there are values smaller than 2.0 mm.day-1 and in 30% the values vary from 2.0 to 8.0 mm.day-1. Also, 13% of the data presented values greater than 8.0 mm.day-1, and 15% presented faults in the data series. Due to the high cloud presence in the rainy season, no Landsat 5 image could be used between 2006 and 2010. However, for RapidEye, due to the high temporal resolution, it was possible to use four images during the rainy season between 2011 and 2016. The coefficient of determination (R2) between the crop coefficient (Kc) obtained by images was 0.57 and 0.41 for the Landsat and RapidEye images, respectively. It is concluded that the increase of soil water stress coefficient may imply a reduction in half of the actual evapotranspiration. Both Landsat 5 and RapidEye presented reasonable performance, but RapidEye images obtained more satisfactory results for evapotranspiration in the dry period. These images are promising in the calculation of evapotranspiration due to high spatial and temporal resolution.